Directive Speech Acts in Online Buying and Selling on Shopee: A Sociopragmatic Study - Musaffak Musaffak; Kisyani Laksono; Mulyono Mulyono; Arif Setiawan (CV. Rustam, 2026)
This study aims to describe the types, strategies, and sociopragmatic functions of directive speech acts in online buying and selling interactions on Shopee. This study employed a qualitative descriptive design supported by descriptive statistical tabulation and content analysis. The qualitative design was used to interpret the social meaning of utterances, while frequency and percentage were used to map the tendency of directive categories in the corpus. The data consisted of 156 directive speech acts taken proportionally from three communication channels: seller-buyer chat features, product reviews, and live promotions. Data classification was conducted using operational coding criteria for eight directive categories and strengthened through contextual checking and inter-coder discussion to maintain coding consistency. The analysis shows that the most dominant type is suggesting, with 45 data points (28.85%), followed by requesting 33 (21.15%), commanding 24 (15.38%), inviting 18 (11.54%), advising 14 (8.97%), prohibiting 9 (5.77%), permitting 7 (4.49%), and urging 6 (3.85%). Direct speech acts appear most frequently, with 92 data points (58.97%), followed by literal indirect speech acts 39 (25.00%) and non-literal indirect speech acts 25 (16.03%). Sociopragmatically, these frequencies serve as an entry point for interpreting power relations, politeness, and persuasion based on utterance context, speaker position, and channel characteristics. The use of “kak,” “mohon,” and familiarity markers is interpreted as a relational strategy that may support trust and rapport, although its direct effect on transaction success requires further empirical testing.